2009
DOI: 10.3382/japr.2008-00101
|View full text |Cite
|
Sign up to set email alerts
|

Administration of mushroom extract to broiler chickens for bifidobacteria enhancement and Salmonella reduction

Abstract: Two experiments were conducted to evaluate the administration of mushroom extract on bifidobacteria and Salmonella populations in broiler chicken feces. In the first experiment, a total of 100 female broiler chicks were assigned to 1 of the following treatment conditions, with 20 chicks per treatment: 1) control (no additive), 2) mushroom extract, 3) vinegar via water, 4) mushroom substrate extract, or 5) milk + water. In experiment 2, a total of 120 female broiler chicks were assigned to 1 of 4 treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Previous studies have reported the addition of probiotics promoted the intestinal health by improving the intestinal bacterial community and the tight junction of the intestines ( Bäumler and Sperandio, 2016 ). Increasing the abundance of Lactobacillus and Bifidobacteria in the gut can inhibit Salmonella infection ( Willis et al., 2009 ; Olnood et al., 2015 ). The energy level of the diet is associated with the Lactobacillus abundance in the gut ( Chen et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the addition of probiotics promoted the intestinal health by improving the intestinal bacterial community and the tight junction of the intestines ( Bäumler and Sperandio, 2016 ). Increasing the abundance of Lactobacillus and Bifidobacteria in the gut can inhibit Salmonella infection ( Willis et al., 2009 ; Olnood et al., 2015 ). The energy level of the diet is associated with the Lactobacillus abundance in the gut ( Chen et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Salmonella infection in broiler chickens mainly causes intestinal health problems that seriously reduce growth performance and increases the spread of drug-resistant genes [5]. The increase of beneficial microorganisms in the intestines, such as Lactobacillus and Bifidobacteria, can against the Salmonella infections [6]. Therefore, changing the composition of gut microbes can be used as a strategy to resist the challenge of Salmonella and improve the growth performance of animals [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Salmonella infection in broiler chicken caused intestinal immune responses and improved the inflammation-related gene expressions of IFNγ , IL-12 , and IL-18 [14]. The resistance to Salmonella can be improved by regulating the intestinal bacteria [6]. A large number of previous studies have focused on the therapeutic effect of antibiotics against S. typhimurium infection [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus). On the other hand, Willis et al (2009) found that herb polysaccharides had effects similar to those of prebiotic.…”
Section: Statisticsmentioning
confidence: 88%